A pico-satellite assembled and tested during the 6th CanSat Leader Training Program - Colín, Ángel (2017)
In this paper, we describe the process to construct a pico-satellite mounted in a bottle of polyethylene terephthalate (PET) of 345 ml. The assembly and tests were made during the 6th CanSat Leader Training Program (CLTP-6) at University Hokkaido-Japan in the summer 2015. The pico-satellite was launched in the facilities of Uematsu Electric Co. Ltd. in Akabira-Japan by a paper model rocket, which achieved a height of approximately 100 m. The mission was designed to measure physical variables, such as temperature and humidity using electronic sensors. During the flight, we observed that the temperature inside the rocket was ∼0.5 ◦C higher than the temperature of the environment. We registered a humidity difference of ∼5%, measured between the maximum height and the landing point. The flight pattern was projected to a plane that covers an area of 50 m × 50 m by means the coordinates of a GPS.